Measuring students' thinking styles to improve the teaching and learning process / Mahfudzah Othman, Zainab Othman and Nor Zalina Ismail - Othman, Mahfudzah; Othman, Zainab; Ismail, Nor Zalina (Universiti Teknologi MARA Cawangan Pahang, 2008)
The study was carried out to introduce the use of techniques and models that can be used to measure students' thinking styles and preferences. This paper discusses the benefits that can be driven from the results of the measurements to improve students' learning process as well as improving lecturers' abilities to deliver knowledge and skills that can meet the students' thinking preferences. This paper also discusses the use of Felder-Silverman Learning Style Model and Thinking Style Questionnaires® that have been widely used in the field of education to measure the thinking preferences. From this study, it is hoped that the teaching and learning environment can be improved and become more effective.